Pengaruh Jumlah Wisatawan, Jumlah Hotel, Tingkat Hunian Hotel dan Jumlah Tenaga Kerja Hotel terhadap Pertumbuhan Ekonomi di Kabupaten Semarang - Rahma Putri Novrianti; Niniek Imaningsih (IPM2KPE, 2023)
hotels, hotel occupancy rates and hotel workforce on economic growth in Semarang Regency. The analytical method used is multiple linear regression analysis using E-views 12 software. The research results show that the number of tourist visits, number of hotels and hotel occupancy rates have a positive and significant effect on economic growth in Semarang Regency. Meanwhile, the number of hotel workers has a negative and significant influence on economic growth in Semarang Regency. Keywords: Hotels, Economic Growth, Hotel Occupancy Rates, Tourists